Structure of corona radiata and tapetum fibers in ventricular surgery. (November 2018) - Yakar, Fatih; Eroglu, Umit; Peker, Elif; Armagan, Ercan; Comert, Ayhan; Ugur, Hasan Caglar
Highlights: Surgery of ventricular lesions requires detailed information regarding white matter fibers. Corona radiata and tapetum fibers were demonstrated by dissecting hemispheres. The location of fibers must be assessed by performing MR tractography. Abstract: In this study the three-dimensional anatomy of the corona radiata and tapetum via the fiber dissection and diffusion tensor imaging of the brain for ventricular surgery was demonstrated. Ten formalin-fixed cerebral hemispheres were dissected for corona radiata and tapetum via Klingler's fiber dissection method under an operating microscope. The corona radiata and tapetum were dissected through lateral and medial surfaces of the cerebral hemisphere, respectively. All surgical routes for ventricular lesions were evaluated for white matter fibers during and after dissections. Corona radiata and tapetum fibers were demonstrated by dissecting hemispheres through lateral and medial aspects of the brain. The internal capsule contains all fibers that extend from thalamus to cortex and cortex to thalamus, brainstem, and spinal cord. These fan-shaped fibers extending from cortex to internal capsule were named the corona radiata. The corona radiata is not a specific pathway, and it is composed of several different fiber pathways. The tapetum contains splenium and body fibers of the corpus callosum. Tapetum is located immediately medial to the ependymal line of the ventricular wall and forms a fiber layer in the medial optical radiation on the coronal and axial sections. Surgical planning for ventricular lesions requires detailed information regarding white matter fibers that can be obtained by the fiber dissection and diffusion tensor imaging of the brain to decrease surgical complications.